2011
DOI: 10.1001/archpediatrics.2011.130
|View full text |Cite
|
Sign up to set email alerts
|

Paternal vs Maternal Kangaroo Care for Procedural Pain in Preterm Neonates

Abstract: Setting: Three university-affiliated level III neonatal intensive care units. Patients: Sixty-two preterm neonates at 28 to 36 weeks' gestational age who were expected to stay in the neonatal intensive care unit for at least 2 blood sampling procedures, without major congenital anomalies, grade III or IV intraventricular hemorrhage, or periventricular leukomalacia; without surgical interventions; not receiving parenteral analgesics or sedatives within 72 hours; and with parental consent. Intervention: During 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 62 publications
3
50
1
4
Order By: Relevance
“…The mean difference in PIPP scores between mothers and fathers was similar to this study; however, the effect size was not reported (3). While this study is too small to support other females to provide kangaroo care for painful procedures, there is nothing in it to suggest that there is a problem if the mother is comfortable with it.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The mean difference in PIPP scores between mothers and fathers was similar to this study; however, the effect size was not reported (3). While this study is too small to support other females to provide kangaroo care for painful procedures, there is nothing in it to suggest that there is a problem if the mother is comfortable with it.…”
Section: Discussionsupporting
confidence: 78%
“…The refusal rate for this study was 52%, substantially higher than in our other studies of kangaroo care for pain, in which the refusal rate has been approximately 20% (3–5,11). Skin‐to‐skin contact is intimate, and many new mothers were not prepared to allow that intimacy to be shared between their baby and an unrelated woman.…”
Section: Discussioncontrasting
confidence: 63%
“…When maternal SSC was compared to nurse SSC, no differences in pain scores at 30, 60, 90, and 120 seconds postlance were found, suggesting that a nurse, too, can give SSC to reduce pain (Johnston et al, 2012). Fathers are not as effective as mothers for the first 60 seconds following heel stick; but at 90 and 120 seconds postheel stick, fathers reduced infant pain as well as mothers (Johnston, Campbell-Yeo, & Filion, 2011). No matter what physiologic measure of pain, nor what pain assessment tool is used, SSC reduces pain.…”
Section: Psychospiritual Realm (Pain and Stress Reduction)mentioning
confidence: 92%
“…The skin-to-skin position with the mother for 30 minutes is more effective for the pain relief of infants than 15 or 80 minutes (Cong, Ludington-Hoe, & Walsh, 2011;Cong et al, 2012). In addition, the findings are inconclusive regarding whether the skin-to-skin position with fathers and others caregivers is as efficient as with mothers in relation to protecting infants against pain experiences (Johnston, Campbell-Yeo, & Filion, 2011;Johnston et al, 2012).…”
Section: Non-pharmacological Management Of Neonatal Painmentioning
confidence: 98%